Carbon-rich nanostructures: The conversion of acetylenes into materials - Chernick, Erin; Tykwinski, Rik (Journal of Physical Organic Chemistry, 2013)
The inherent thermodynamic instability of the carbon-carbon triple bond offers a unique starting point for the formation of carbon-rich nanomaterials, which are of increasing importance for use in materials science and technology. Whereas significant efforts have recently been devoted toward suppressing the well-known reactivity of sp-hybridized compounds in an effort to obtain the elusive carbon allotrope "carbyne," this mini-review will focus on the opposite idea; that is, we explore current research efforts that attempt to harness the reactivity of carbon-carbon triple bonds in a controlled, templated manner that ultimately converts acetylenic precursors into ordered, carbon-based nanomaterials. Copyright © 2013 John Wiley & Sons, Ltd.